Public Administration as One of the Forms for Exercising State Power - Serohina, Svitlana Hryhorivna; Mykolenko, Olena Mykolayivna; Seliukov, Vadym; Lialiuk, Oleksii (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
The problematic issues related to the definition of public administration as one of the forms of exercising state power are considered. The level of how the quality of public administration processes affects the functioning of the state system and its key mechanisms is analyzed. An important emphasis is placed on the fact that the most useful of the successful practices of public administration in developed countries can be adopted for the state system of Ukraine. Modern problems and ways of their effective solution at different levels of state and local administration are actualized. The analysis of the basic structural elements of qualitative public administration, the level of their influence on processes of realization of the state-power powers within functioning of the state system is offered. For example, it explains whether transparency and impartiality do have a significant impact on the efficiency of public administration. The efficiency (effectiveness) of various,